2017
DOI: 10.1177/0959680117740777
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-term employment in Norway and Sweden: A pathway to labour market marginalization?

Abstract: We compare the effects of relatively liberal regulations on the use of temporary employment in Sweden and more restrictive rules in Norway. We find not only that temporary work may be a stepping stone out of unemployment but also that fixed-term employees are exposed to significant risks of long-term marginalization. Moreover, fixed-term employees in Sweden face greater risks of long-run unemployment and low earnings compared to those in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
22
0
2
Order By: Relevance
“…Still, the stricter rules in Norway were supported by stronger cognitive and normative sentiments about permanent contracts, as well as trade unions more actively sanctioning high shares of temporary workers (with the exception of warehouses). Svalund and Berglund (2017), studying those holding a fixed-term contract 5 years later, find that the risk of marginalization is higher in Sweden. Studying hiring processes at company level, we find that with the more lenient regulation of fixed-term work and TAW in Sweden, the threshold and criteria for reactive ad-hoc use and more strategical hiring of temporary workers appear to be somewhat lower among the Swedish companies.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the stricter rules in Norway were supported by stronger cognitive and normative sentiments about permanent contracts, as well as trade unions more actively sanctioning high shares of temporary workers (with the exception of warehouses). Svalund and Berglund (2017), studying those holding a fixed-term contract 5 years later, find that the risk of marginalization is higher in Sweden. Studying hiring processes at company level, we find that with the more lenient regulation of fixed-term work and TAW in Sweden, the threshold and criteria for reactive ad-hoc use and more strategical hiring of temporary workers appear to be somewhat lower among the Swedish companies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strictness of the two types of EPL should not be considered separately, and central factor is the gap between the two (Barbieri and Cutuli, 2016;Dieckhoff and Steiber, 2012;Svalund and Berglund, 2018). In a situation of partial deregulation or flexibilization at the margin, where EPL-temporary has been liberalized while EPLregular remains strict (a large 'EPL-gap'), both the buffer and the screening functions imply that employers have an added incentive to offer renewals of temporary contracts instead of converting them into permanent ones (Blanchard and Landier, 2002;Noelke, 2016).…”
Section: Employment Protection Legislationmentioning
confidence: 99%
“…11 All of the above studies control for observed individual heterogeneity and unobserved time-invariant heterogeneity. A related study for Sweden and Norway examines the long-term probabilities of low earnings, defined as having less than 50% of median earnings 5 years later (Svalund and Berglund 2018). The differences in the probabilities of low earnings between those initially on fixedterm contracts and in permanent jobs turn out to be modest for Sweden and even smaller for Norway (2-5 and 1-2 percentage points, respectively).…”
Section: Econometric Analysis Of the Wage Premium For Fixed-term Emplmentioning
confidence: 99%